Analisis Penerapan Sistem Informasi Akuntansi (SIA) Sederhana Berbasis Aplikasi Pada UMKM Orang Asli Papua Di Kota Jayapura - Rosalin Ledi Diana Anouw; Kurniawan Patma; Hesty T. Salle (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2025)
This research analyzes the implementation of an accounting information system using the Buku Warung application for Mama-Mama Papua handicraft MSMEs in Abepura District, Jayapura. Using a qualitative case study approach, data were collected through interviews, observation, and documentation from 20 participants along Jalan Raya Abepura. Ten participants owned Android phones and joined the Buku Warung training, while the other ten were interviewed regarding their understanding of record-keeping. Analysis employed Miles’ model before and after implementation. Findings show that prior to adoption, 70% of participants had never kept records, mixed personal and business funds, and relied on memory, due to lack of knowledge, time constraints, and manual systems. After implementation, Android users operated the application, managing stock, recording transactions, and accessing reports. Positive impacts included efficiency recording, accuracy, cash flow monitoring, digital literacy, and the ability to analyze profits and losses for improved financial control and decision-making.